Seasonal Meandering of the Polar Front Upstream of the Kerguelen Plateau. Issue 18 (25th September 2018) - Pauthenet, E.; Roquet, F.; Madec, G.; Guinet, C.; Hindell, M.; McMahon, C. R.; Harcourt, R.; Nerini, D.
Abstract: The location of the Antarctic Polar Front (PF) is mapped in the Southern Indian Ocean by decomposing the shape of temperature and salinity profiles into vertical modes using a functional Principal Component Analysis. We define the PF as the northernmost minimum of temperature at the subsurface and represent it as a linear combination of the first three modes. This method is applied on an ocean reanalysis data set and on in situ observations, revealing a seasonal variability of the PF latitudinal position that is most pronounced between the Conrad Rise and the Kerguelen Plateau. This shift coincides with variations in the transport across the Northern Kerguelen Plateau. We suggest that seasonal changes of the upper stratification may drive the observed variability of the PF, with potentially large implications for the pathways and residence time of water masses over the plateau and the phytoplankton bloom extending southeast of the Kerguelen Islands. Plain Language Summary: The Antarctic Polar Front (PF) is a water mass boundary that flows around Antarctica between approximately 48°S and 56°S in the Southern Indian Ocean. The position of the PF in space and time is important to understand the oceanic circulation, the heat and salt exchanges, and also marine ecosystems. In the Indian sector the PF has to cross the Kerguelen Plateau, a major bottom topography feature. The present study develops and then applies a novel method for mapping the PF taking into account the whole hydrographic structure in the upper 300 m of the ocean. We are able to map the PF position and find that it presents large seasonal variations that are more intense just west of the Kerguelen Plateau. Between the Conrad Rise and the Kerguelen Plateau, the PF is essentially zonally orientated in September and found farther south by up to 4° latitude in March. Shifts in the PF position are shown to correlate with a seasonal variation in volume transport between Kerguelen and Heard Islands. We discuss how these seasonal variations in circulation pathways could have an impact on the local marine ecosystems. Key Points: A novel method classifying TS profiles reveals the spatiotemporal variability of the Polar Front (PF) in the Southern Indian Ocean West of the Kerguelen Plateau, the Polar Front follows the 49 degrees south latitude in the Austral spring, while in the autumn it is located at 53 degrees south This seasonal meandering covaries with the transport over the Plateau, suggesting important variations in circulation pathways